Carex jianfengensis (Carex sect. Rhomboidales, Cyperaceae), a New Species from Hainan, China - Yang, Hubiao (PLoS One, 2015)
A new species of Carex sect. Rhomboidales, C. jianfengensis, is described and illustrated from Hainan, China. The new species is similar to C. zunyiensis but differs in having involucral bracts sparsely hispid and with ca.1 cm long sheaths; inflorescence with 4 spikes, terminal spike ca. 2.5 cm long, lateral spikes 2–3.5 × 0.7–1 cm; staminate glumes narrowly ovate, ca. 5 mm; pistillate glumes triangular-lanceolate, 5–7 mm; perigynia 6–8 × 3 mm and pubescent on veins; nutlet 4–5 mm long, rhombic-ovoid, trigonous, base with shortly stipitate, apex abruptly contracted into a erect short beak, and not expanding into an annulate orifice.